0
$\begingroup$

I have to proof the following thing and I am completely stuck.: Let $a=a_0\in\mathbb{R}$ and $b=b_0\in\mathbb{R}$ be postive and $a<b$.

Let $a_{n+1}=\sqrt{(a_n b_n)}$ and $b_{n+1}=\frac{a_n +b_n}{2}$.

Proof that: $a_{n+1}\geq a_n$ and $b_n\geq b_{n+1}$.

I know that $\sqrt{{{(a_n b_n)}}}\leq\frac{a_n +b_n}{2}$.

If I use this formula it is quite easy to show that $a_{n+1}\geq a_n$ and $b_n\geq b_{n+1}$. But is that enough? Don't I have to give a proof using induction? I would be very grateful for any help! Thank you very much in advance.

$\endgroup$
  • 1
    $\begingroup$ Induction is not a must. You could use any method as long as it is acceptable mathematically. $\endgroup$ – Jlamprong May 14 '14 at 19:23
  • $\begingroup$ But I still dont see how using the formula proofs it for all n. $\endgroup$ – Hans May 14 '14 at 19:30
0
$\begingroup$

That $a_n > 0$ and $b_n > 0$ can be assumed to be true or proven from their respective recursive formulas. $a_{n+1} = \sqrt{a_nb_n} \geq \sqrt{a_n^2} = a_n$, because $b_n \geq a_n$, and the latter inequality is true due to the AM-GM inequality. $b_n - b_{n+1} = \dfrac{b_n - a_n}{2} \geq 0$ since $b_n \geq a_n$ is true also due to AM-GM inequality.

Note: $b_n = \dfrac{a_{n-1} + b_{n-1}}{2} \geq \sqrt{a_{n-1}b_{n-1}} = a_n$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.